Drug prescription pattern of hypertension patients at primary healthcare facilities in West Denpasar - Kartiga Silvaraju; I Gusti Ayu Artini (DiscoverSys Inc., 2020)
Background: In the treatment of hypertension, investigating and monitoring the prescription patterns of antihypertensive medications time by time is essential to assess the adherence to treatment guidelines. Inappropriate prescribing negatively impacts on health and economy of individual and the society.Aim: The study aims to know the antihypertensive prescribing pattern of hypertension patients at primary healthcare facilities.Method: This studyis a descriptive study with cross sectional design as well as concern to the drug prescribing pattern of hypertension in both 1st and 2nd West Denpasar primary healthcare (PHC), Bali as many as 54 samples from January-December 2016.Result: Mean age is between 60-69 years old, and female were more prone to hypertension than male.Conclusion: The study revealed that the prescription of antihypertensive medication in West Denpasar primary healthcare was related to JNC guidelines, except monotherapy of diuretics.